Life course socioeconomic position, alcohol drinking patterns in midlife, and cardiovascular mortality: Analysis of Norwegian population-based health surveys - Degerud, Eirik (PLoS Med, 2018)
BACKGROUND: Socioeconomically disadvantaged groups tend to experience more harm from the same level of exposure to alcohol as advantaged groups. Alcohol has multiple biological effects on the cardiovascular system, both potentially harmful and protective. We investigated whether the diverging relationships between alcohol drinking patterns and cardiovascular disease (CVD) mortality differed by life course socioeconomic position (SEP). METHODS AND FINDINGS: From 3 cohorts (the Counties Studies, the Cohort of Norway, and the Age 40 Program, 1987–2003) containing data from population-based cardiovascular health surveys in Norway, we included participants with self-reported information on alcohol consumption frequency (n = 207,394) and binge drinking episodes (≥5 units per occasion, n = 32,616). We also used data from national registries obtained by linkage. Hazard ratio (HR) with 95% confidence intervals (CIs) for CVD mortality was estimated using Cox models, including alcohol, life course SEP, age, gender, smoking, physical activity, body mass index (BMI), systolic blood pressure, heart rate, triglycerides, diabetes, history of CVD, and family history of coronary heart disease (CHD). Analyses were performed in the overall sample and stratified by high, middle, and low strata of life course SEP. A total of 8,435 CVD deaths occurred during the mean 17 years of follow-up. Compared to infrequent consumption (<once/month), moderately frequent consumption (2–3 times per week) was associated with a lower risk of CVD mortality (HR = 0.78, 95% CI 0.72, 0.84) overall. HRs for the high, middle, and low strata of SEP were 0.66 (95% CI 0.58, 0.76), 0.87 (95% CI 0.78, 0.97), and 0.79 (95% CI 0.64, 0.98), respectively, compared with infrequent users in each stratum. HRs for effect modification were 1.30 (95% CI 1.10, 1.54, p = 0.002; middle versus high), 1.23 (95% CI 0.96, 1.58, p = 0.10; low versus high), and 0.96 (95% CI 0.76, 1.21, p = 0.73; low versus middle). In the group with data on binge drinking, 2,284 deaths (15 years) from CVDs occurred. In comparison to consumers who did not binge during the past year, HRs among frequent bingers (≥1 time per week) were 1.58 (95% CI 1.31, 1.91) overall, and 1.22 (95% CI 0.84, 1.76), 1.71 (95% CI 1.31, 2.23), and 1.85 (95% CI 1.16, 2.94) in the strata, respectively. HRs for effect modification were 1.36 (95% CI 0.87, 2.13, p = 0.18; middle versus high), 1.63 (95% CI 0.92, 2.91, p = 0.10; low versus high), and 1.32 (95% CI 0.79, 2.20, p = 0.29; low versus middle). A limitation of this study was the use of a single measurement to reflect lifetime alcohol consumption. CONCLUSIONS: Moderately frequent consumers had a lower risk of CVD mortality compared with infrequent consumers, and we observed that this association was more pronounced among participants with higher SEP throughout their life course. Frequent binge drinking was associated with a higher risk of CVD mortality, but it was more uncertain whether the risk differed by life course SEP. It is unclear if these findings reflect differential confounding of alcohol consumption with health-protective or damaging exposures, or differing effects of alcohol on health across socioeconomic groups.